Five new species of Ishiharella Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae) with a key to worldwide species of the genus - Yu, Xiaofei; Yang, Maofa; Dietrich, Christopher H (Zootaxa, 2015)
Detailed morphological descriptions and illustrations of five new species of the empoascine leafhopper genus Ishiharella Dworakowska (Typhlocybinae: Emposascini): I. dentidensa Yu & Yang, sp. nov., I. falcata Yu, Yang & Dietrich, sp. nov., I. hirsuta Yu, Yang & Dietrich, sp. nov., I. inflata Yu & Yang, sp. nov. and I. multiprotrusa Yu, Yang & Dietrich, sp. nov. are provided and a key to species of the genus is given.